2013
DOI: 10.1136/thoraxjnl-2012-202230
|View full text |Cite
|
Sign up to set email alerts
|

Phase II studies of nebulised Arikace in CF patients withPseudomonas aeruginosainfection

Abstract: RationaleArikace is a liposomal amikacin preparation for aerosol delivery with potent Pseudomonas aeruginosa killing and prolonged lung deposition.ObjectivesTo examine the safety and efficacy of 28 days of once-daily Arikace in cystic fibrosis (CF) patients chronically infected with P aeruginosa.Methods105 subjects were evaluated in double-blind, placebo-controlled studies. Subjects were randomised to once-daily Arikace (70, 140, 280 and 560 mg; n=7, 5, 21 and 36 subjects) or placebo (n=36) for 28 days. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
137
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(140 citation statements)
references
References 24 publications
1
137
0
2
Order By: Relevance
“…The results of the phase II clinical trial have been published and showed a durable improvement in lung function and a reduced P. aeruginosa sputum count. [62] Furthermore, Arikace® is also being investigated as a treatment for nontuberculous mycobacterial lung disease (phase II clinical trial) and for non-CF bronchiectasis patients with P. aeruginosa lung infections (phase II clinical trial), which both likely involve biofilm formation. No clinical data are available at this moment.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The results of the phase II clinical trial have been published and showed a durable improvement in lung function and a reduced P. aeruginosa sputum count. [62] Furthermore, Arikace® is also being investigated as a treatment for nontuberculous mycobacterial lung disease (phase II clinical trial) and for non-CF bronchiectasis patients with P. aeruginosa lung infections (phase II clinical trial), which both likely involve biofilm formation. No clinical data are available at this moment.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Amikacin concentrations in sputum were about 45-fold higher upon aerosolized administration of 500 mg of a liposomal formulation than after parenteral administration of 30 mg/kg of body weight; mean sputum concentrations increased ϳ3-to 5-fold from day 1 to day 14 (170,171). In supplemental material published previously (158), it was reported that mean serum concentrations as low as 1.29 g/liter and mean sputum concentrations of 2,286 g/g were recorded following aerosolized administration of 560 mg (171).…”
Section: Serum and Sputum Pharmacokineticsmentioning
confidence: 99%
“…In supplemental material published previously (158), it was reported that mean serum concentrations as low as 1.29 g/liter and mean sputum concentrations of 2,286 g/g were recorded following aerosolized administration of 560 mg (171).…”
Section: Serum and Sputum Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on in vitro studies, liposomes demonstrate excellent penetration into CF sputum and P. aeruginosa biofilms (63). A phase 2 clinical trial in CF supported preliminary pharmacokinetics, safety, and efficacy of this therapy; we are awaiting the results of a European/Canadian comparator trial (64).…”
Section: Inhaled Antibiotics Currently Used In Clinical Practicementioning
confidence: 99%